(3EJMGa GdeMHjf HLhGQ eG jaYd aj GdNeGSjf ef UHZ GdHjV hZjQgs - (3EHQGgje Hf QeVGf GdNVQjs
(3ChdgG (B:s
(3hHYO abO hbY ai eLdS HYV GdCeQGA GdYXGe hGdcHQGA GdaNGe gh GdCejQ ESeGYjd WGFaI GdLQGcSI YeG jaYd ai eUQ hZjQgG ai HYV GdHdGO ai Chd GdNeGSjf s
(3BNQgG (B:s
(3aYde ef eLehY eG PcQ Cf eG jaYdg Cgd eUQ dG caQ ajg Hd hdG EcQGgg EdG Cf jchf ajg dgh hdYH dCf GdcQGgjI JMJGL Edi Pdjd hGddg SHMGfg CYde s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY WdYJ (B661) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs